2021
DOI: 10.1055/a-1345-3626
|View full text |Cite
|
Sign up to set email alerts
|

European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB): An Update on the Pediatric CEUS Registry on Behalf of the “EFSUMB Pediatric CEUS Registry Working Group”

Abstract: The European Federation of Ultrasound in Medicine and Biology (EFSUMB) created the “EFSUMB Pediatric Registry” (EFSUMB EPR) with the purpose of collecting data regarding the intravenous application of pediatric contrast-enhanced ultrasound (CEUS). The primary aim was to document the current clinical practice and usefulness of the technique and secondarily to assess CEUS safety in children. We issue the preliminary results of this database and examine the overall practice of CEUS in children in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 80 publications
0
13
0
1
Order By: Relevance
“…The possible differential diagnostic option in children with focal renal infection, particularly in the early stage of abscess formation, is Wilms tumour, which has a more non-homogenous hyperenhancement of tumour tissue, usually with multiple non-enhanced areas of necrosis, various sizes and shapes. 9–11 A focal nephritis has to be differentiated from renal cell carcinoma which is hypoenhanced, but has fast washout, while in inflammatory lesions there is slow washout on delayed images. 7 On the other hand, CEUS can exclude focal renal infection by diagnosing pseudolesion, which has a similar enhancement pattern as normal kidney parenchyma, and direct the investigation searching for other infectious foci.…”
Section: Discussionmentioning
confidence: 99%
“…The possible differential diagnostic option in children with focal renal infection, particularly in the early stage of abscess formation, is Wilms tumour, which has a more non-homogenous hyperenhancement of tumour tissue, usually with multiple non-enhanced areas of necrosis, various sizes and shapes. 9–11 A focal nephritis has to be differentiated from renal cell carcinoma which is hypoenhanced, but has fast washout, while in inflammatory lesions there is slow washout on delayed images. 7 On the other hand, CEUS can exclude focal renal infection by diagnosing pseudolesion, which has a similar enhancement pattern as normal kidney parenchyma, and direct the investigation searching for other infectious foci.…”
Section: Discussionmentioning
confidence: 99%
“…Liver incidentalomas are commonly encountered with a reported frequency of up to 33% of radiological studies and 50% of autopsies in adult patients [ 11 , 12 ], but they are rarely reported in children. The reasons are manifold and have been discussed in detail elsewhere [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Definitionmentioning
confidence: 99%
“…The most important indications for using CEUS include: the characterization of indeterminate focal liver lesions using conventional B-mode ultrasound, computed tomography and in staging, and follow-up of previously known focal liver lesions (FLL). The latter includes pediatric patients with known cancer, patients who are under a surveillance program for chronic liver disease or other conditions that predispose them to malignancy [ 16 , 17 , 19 ], and patients who have undergone interventional procedures (e.g., post chemotherapy, or ablation) [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Definitionmentioning
confidence: 99%
“…Microbubble contrast-enhanced ultrasound (CEUS) is a well-established safe, low-cost, and efficient imaging modality [9][10][11][12][13][14]. Microbubbles of ultrasound contrast agents (UCA) remain intravascular without diffusing into the interstitial space and are easily visible compared to the adjacent tissue, thus improving visibility of very small vascular structures.…”
Section: Accepted Manuscriptmentioning
confidence: 99%